KETERTARIKAN SISWA PADA MATA PELAJARAN EKONOMI KELAS XI LINTAS MINAT EKONOMI DI SMA NEGERI 1 LAWANG TAHUN AJARAN 2016/2017 - Wahyu Nila Megasari (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This study aims to determine the causes of student interest in economic subjects on the class XI economy cross-interest in SMAN 1 Lawang and to determine whether the main factor in making students interested in economic subjects. The research method used is qualitative research with phenomenology approach. Data collection is done by interview and documentation. Judging from teacher or teacher factor is high. It can be seen from the interview that the students are very interested in the way the teacher teaches a nice, relaxed and not boring. Students' interest in the subjects of economics through teaching material factors is also high. This can be seen from the interviews that the teaching materials used are very clear and easy to understand. In terms of media, interest in terms of media used by teachers is high. It can be seen from the results of interviews that the media used by teachers in conveying materials because the teacher uses the media power point and sometimes also use the video in delivering the material. Judging from the factors of educational facilities is also very interesting. Students say that the facilities provided are very complete. DOI: https://dx.doi.org/10.17977/UM014v10i22017p149